Yeast ribosomal protein S33 is encoded by an unsplit gene. - Leer, R J (1983)
The structure of the gene coding for ribosomal protein S33, - a protein which escapes the coordinate control of ribosomal protein synthesis in rna 2 mutant cells -, was determined by sequence analysis. The gene comprises an uninterrupted coding region of 204 nucleotides encoding a protein of 8.9 kD. Like for other yeast ribosomal protein genes that have been sequenced so far, a relatively strong codon bias was observed. By S1 nuclease mapping the 5' end of the S33 mRNA was shown to be located at 11 to 15 nucleotides upstream from the initiation codon.